BASIC PRINCIPLES, FORMS AND METHODS OF FINANCIAL SECURITY PROVISION OF LOCAL COMMUNITY DEVELOPMENT - Sukharska L.V. (Pressing Problems of Public Administration, 2016)
The article de nes the set of the fundamental principles and the mutual consistency of such fundamentalprinciples, forms and methods of  nancial provision for the development of the local communities.It is proposed to break down such principles into the principles of the budgetary management, theprinciples of the  scal regulation, and the principles of local government performance, and to breakdown the methods into the methods, related to the attraction of the  nancial resources and methods,related to the management of the  nancial resources. And the systemic use of such principles andmethods in the local development strategies is proposed.